2017
DOI: 10.1016/j.jvoice.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Strength as an Outcome Measure for Treatment of Dysphonia

Abstract: Background Measurement of treatment outcomes is critical for of the spectrum of voice treatments, (i.e., surgical, behavioral, or pharmacological). Outcome measures typically include visual (e.g., stroboscopic data), auditory (e.g., CAPE-V, GRBAS), and objective correlates of vocal fold vibratory characteristics, such as acoustic signals (e.g., harmonics-to-noise ratio, cepstral peak prominence) or patient self-reported questionnaires (e.g., Voice Handicap Index, Voice-Related Quality of Life). Subjective meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The results of our APA concur with previous studies; we observed a wide variability in the degree of voice deviation that was not related to the etiology of dysphonia 1 , 2 , 17 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of our APA concur with previous studies; we observed a wide variability in the degree of voice deviation that was not related to the etiology of dysphonia 1 , 2 , 17 .…”
Section: Discussionsupporting
confidence: 92%
“…According to reports in the scientific literature, in addition to the anatomical and physiological issues that predispose women to voice disorders 21 , women seek medical care more often than men 23 , 24 ; furthermore, some voice disorders are more prevalent in female patients 25 . Kopf et al 17 analyzed 30 cases of dysphonia and found that the most common diagnoses in women were muscle tension, functional disorders, and mass lesions of the vocal folds. Other studies also found a greater prevalence of dysphonia in adult women 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to capture the quality of a vibration, pitch strength was also estimated (Camacho and Harris 2008). Pitch strength is a psychoacoustic construct of the pitch saliency of a sound (the degree that a tone can be heard in a sound) which is similar to a periodicity measure and correlates to perceptual voice quality (Kopf et al 2017). Fundamental frequency (f 0 ) and pitch strength were calculated from the glottal flow waveform for each signal using the Aud-SWIPE pitch estimation algorithm (Camacho 2012) in MATLAB.…”
Section: Discussionmentioning
confidence: 99%